Uji Beberapa Konsentrasi Ekstrak Tepung Daun Bintaro (Cerbera manghas L.) Mengendalikan Keong Mas (Pomacea canaliculata L.) pada Tanaman Padi (Oryza sativa L. ) - Muhammad Tuah Alamin Hasibuan; Hafiz Fauzana (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
This study aims to obtain the best concentration of bintaro leaf flour extract to control golden snails in rice plants. This research was conducted using a Completely Randomized Design (CRD) with 5 treatments and 4 replications, so that 20 experimental units obtained. Each unit of experiment was infested with 10 golden snails aged 30 days. The treatments given several concentrations of bintaro leaf extract, namely 0 g.l-1 water, 25 g.l-1 water, 50 g.l-1 water, 75 g.l-l water, and 100 g.l-1 water. The parameters observed were initial time of death (hours), lethal time 50 (LT50) (hours), daily mortality (%), total mortality (%) and daily temperature and humidity of the study site. Data were analyzed statistically using analysisof variance and further tests with the Least Significant Difference (LSD). The results showed that the extract of bintaro leaves given at the highest concentration off 100 g.l-1 of water produced the golden snail mortality which tended to be the best with the fastest initial death at 93,75 hours, the fastest lethal time 50 at 155,25 hours, the highest daily mortality percentage of 22% and total mortality by 65% for 168 hours of observation, but not yet effective in turning off golden snails by more than 80%.Keywords: Rice plants, golden snail (Pomacea canaliculata L.), botanical insecticide